SYUBHAT DALAM KAJIAN HADIS - Sri Ulfa Rahayu (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
Halal and haram are clear. But there is one thing that is between it and it is rarely known with certainty what it means and  how we respond to things that are not yet known between halal and haram. The aim of this research is to find out the Hadith about doubtfulness and the quality of the Hadith. This can be done with content analysis by compiling the appropriate Hadith and then explaining the sanad and the contents of the Hadith whether it contradicts the Qur'an or other Hadith and the authenticity of the Hadith. The results obtained that the Hadith about doubtful sahih, the contents are sahih. This finding can be used as a source of law in carrying out a job by looking at halal and haram and the law between the two.